Folic Acid Attenuates Glial Activation in Neonatal Mice and Improves Adult Mood Disorders Through Epigenetic Regulation - Zhao, Tiantian; Wu, Dong; Du, Jingyi; Liu, Guowei; Ji, Guangyu; Wang, Zixiao; Peng, Fan; Man, Lajie; Zhou, Wenjuan; Hao, Aijun (Frontiers in Pharmacology, 2022)
Growing evidence indicates that postnatal immune activation (PIA) can adversely increase the lifetime risk for several neuropsychiatric disorders, including anxiety and depression, which involve the activation of glial cells and early neural developmental events. Several glia-targeted agents are required to protect neonates. Folic acid (FA), a clinical medication used during pregnancy, has been reported to have neuroprotective properties. However, the effects and mechanisms of FA in PIA-induced neonatal encephalitis and mood disorders remain unclear. Here, we investigated the roles of FA in a mouse model of PIA, and found that FA treatment improved depressive- and anxiety-like behaviors in adults, accompanied by a decrease in the number of activated microglia and astrocytes, as well as a reduction in the inflammatory response in the cortex and hippocampus of neonatal mice. Furthermore, we offer new evidence describing the functional differences in FA between microglia and astrocytes. Our data show that epigenetic regulation plays an essential role in FA-treated glial cells following PIA stimulation. In astrocytes, FA promoted the expression of IL-10 by decreasing the level of EZH2-mediated H3K27me3 at its promoter, whereas FA promoted the expression of IL-13 by reducing the promoter binding of H3K9me3 mediated by KDM4A in microglia. Importantly, FA specifically regulated the expression levels of BDNF in astrocytes through H3K27me3. Overall, our data support that FA may be an effective treatment for reducing mood disorders induced by PIA, and we also demonstrated significant functional differences in FA between the two cell types following PIA stimulation.